Local Flaps with Negative Pressure Wound Therapy in Secondary Reconstruction of Myelomeningocele Wound Necrosis - Chihena H. Banda, MD; Mitsunaga Narushima, MD, PhD; Ryohei Ishiura, MD; Minami Fujita, MD; Megumi Furuya, MD (Plastic and Reconstructive Surgery, Global Open, 2018)
Summary:. Major wound necrosis is an uncommon yet critical complication of meningomyelocele surgical repair with few reports available. Management is demanding and often requires further reconstructive surgery. We report a case of a neonate who developed extensive wound necrosis with dehiscence following primary repair of myelomeningocele. The large defect was reconstructed using transposition fasciocutaneous flaps and negative pressure wound therapy applied over the flap donor sites resulting in wound closure, alleviating the need for further surgery. We report this case to highlight the importance of local flap design in reconstruction of the complex wounds seen following meningomyelocele repair wound necrosis. Additionally, we report the unique utilization of negative pressure wound therapy in the management of myelomeningocele.